(untitled) (Balkan Journal of Applied Mathematics and Informatics, 2021)
Mathematical modelling is tool for presenting objects and processes with mathematical language and mathematical rules. Mathematical models can be used for research in public health and epidemiology. Nowadays, during COVID19 outbreak, mathematical modelling is playing a central role in controlling spread of infection, making prediction that can help monitoring of epidemic and making adequate responses, in order to lower the number of new infections. In this paper, several models, commonly used for control of spreading of infections are considered. These models can also help controlling COVID 19 infections.